EFFECTIVENESS OF EXTRACORPOREAL SHOCK WAVE THERAPY (ESWT) IN THE MANAGEMENT OF SPASTICITY POST-STROKE: A CLINICAL EVALUATION - Dr. Pawan Sharma; Dr. Sonu Singh; Dr. Maan Singh; Dr. Dwit Vora (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Spasticity following stroke significantly impairs motor function and impacts quality of life. Current interventions, including pharmacological treatments, physical therapy, and surgical options, have demonstrated limited effectiveness and potential side effects. Extracorporeal shock wave therapy (ESWT) is gaining attention as a non-invasive option for spasticity management. This study assessed the efficacy of ESWT in reducing spasticity and enhancing motor function and quality of life in stroke survivors through a randomized controlled trial. Eighty participants were randomly assigned to receive either ESWT or standard care, with spasticity and motor function assessed using the Modified Ashworth Scale (MAS) and Fugl-Meyer Assessment (FMA), while quality of life was evaluated with the Stroke-Specific Quality of Life Scale (SSQOL). Post-treatment results showed significant spasticity reduction in the ESWT group, alongside notable improvements in motor function and quality of life. The findings suggest that ESWT is a viable, non-invasive option for enhancing spasticity management in stroke rehabilitation.